Biorefining of rice straw by sequential fermentation and anaerobic digestion for bioethanol and/or biomethane production: Comparison of structural properties and energy output. (November 2018) - Elsayed, Mahdy; Abomohra, Abd El-Fatah; Ai, Ping; Wang, Dianlong; El-Mashad, Hamed M.; Zhang, Yanlin
Graphical abstract: Highlights: Three routes of rice straw conversion were studied. Sequential fermentation and anaerobic digestion (AD) enhanced fibers degradation. Fermentation by second route resulted in ethanol yield of 87.4 g kg −1 dry straw. The maximum biogas yield of 372.4 L kg −1 VS was recorded by AD through third route. The highest bioenergy output and energy conversion efficiency were obtained by third route. Abstract: Three routes; namely R1 representing direct anaerobic digestion (AD), R2 representing enzymatic hydrolysis followed by fermentation, distillation, then AD, and R3 representing AD of fermentation broth without distillation; of alkali pretreated rice straw were investigated. Results showed that sequential fermentation and AD effectively enhanced fibers degradation with significant changes in the composition. Fermentation through R2 resulted in ethanol yield of 87.4 g kg −1 dry straw. Maximum biogas yields of 286.9, 233.3 and 372.4 L kg −1 VS were recorded by AD for R1, R2 and R3 after reaching the steady state at 36, 24 and 33 days, respectively. However, biogas produced through R3 showed the highest significant biomethane content (79.3%) which represented 15 and 8% higher than that of R1 and R2, respectively. Therefore, the highest bioenergy output and energy conversion efficiency of 10.58 GJ ton −1 and 75.6%, respectively, were obtained through R3 demonstrating the positive effect of fermentation prior to AD.